2018
DOI: 10.1002/cpmo.40
|View full text |Cite
|
Sign up to set email alerts
|

Engineering Point Mutant and Epitope‐Tagged Alleles in Mice Using Cas9 RNA‐Guided Nuclease

Abstract: Mice carrying patient-associated point mutations are powerful tools to define the causality of single-nucleotide variants to disease states. Epitope tags enable immuno-based studies of genes for which no antibodies are available. These alleles enable detailed and precise developmental, mechanistic, and translational research. The first step in generating these alleles is to identify within the target sequence-the orthologous sequence for point mutations or the N or C terminus for epitope tags-appropriate Cas9 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 78 publications
1
20
0
Order By: Relevance
“…Blue and orange bars represent deletions and insertions, respectively.), in agreement with reports that analyzed deletion or knock-in alleles in mice [35,36,37]. Droplet digital PCR or qPCR can be used as an alternative to WGS or standard PCR for copy counting of donor template DNA in founder mouse offspring, as template oligonucleotides can be randomly inserted into the genome [36, 38,39,40]. A report using several cell lines, including mouse ES cells, showed that Cas9 activity at on-target sites resulted in large deletions up to several kilobases long or complex lesions with segments from another chromosome in over 10% of the recovered alleles [11].…”
Section: How Can We Screen Out Unexpected “On-target Effects”?supporting
confidence: 75%
“…Blue and orange bars represent deletions and insertions, respectively.), in agreement with reports that analyzed deletion or knock-in alleles in mice [35,36,37]. Droplet digital PCR or qPCR can be used as an alternative to WGS or standard PCR for copy counting of donor template DNA in founder mouse offspring, as template oligonucleotides can be randomly inserted into the genome [36, 38,39,40]. A report using several cell lines, including mouse ES cells, showed that Cas9 activity at on-target sites resulted in large deletions up to several kilobases long or complex lesions with segments from another chromosome in over 10% of the recovered alleles [11].…”
Section: How Can We Screen Out Unexpected “On-target Effects”?supporting
confidence: 75%
“…All single guide (sgRNAs) were synthesized as described by Gertsenstein and Nutter (2018). Injection mixes for pronuclear injections included 10 ng/µl of each sgRNA and 20 ng/µl of Cas9 mRNA (Life Technologies; A23978) (Gertsenstein and Nutter, 2018).…”
Section: Synthesis Of Sgrnas and Cas9 Mrnamentioning
confidence: 99%
“…Post-birth, founders can be screened by long-range genotyping PCR using one primer within the insert and one primer outside the homology arm, similar to the procedure we have previously described (Gu, Posfai, & Rossant, 2018). Positive founders should be further validated by Sanger sequencing of the knock-in allele and copy number analysis (Current Protocols article: Gertsenstein & Nutter, 2018). , pH 7.4, 0.25…”
Section: Of 15mentioning
confidence: 99%